NEONATAL DYSFUNCTIONS RESPONSIBLE (EVENTUALLY) FOR DEFINITIVE NEUROLOGICAL HANDICAPS - Andrei Zamfirescu (Amaltea Medical Publishing House, 2009)
Beside several malformations, especially cerebral (neurulation disorders, agenesia of the corpus callosum, neuronal migration disorders, etc.), the main neonatal causes of neurological sequelar handicaps are: hipoxya, intracerebral hemorrhage, nuclear icterus, hypoglycemia, CNS infections, and iatrogenic pathology.